A definition for gamification: anchoring gamification in the service marketing literature - Kai Huotari; Juho Hamari (Germany, 2022)
“Gamification” has gained considerable scholarly and practitioner attention; however, the discussion in academia has been largely confined to the human–computer interaction and game studies domains. Since gamification is often used in service design, it is important that the concept be brought in line with the service literature. So far, though, there has been a dearth of such literature. This article is an attempt to tie in gamification with service marketing theory, which conceptualizes the consumer as a co-producer of the service. It presents games as service systems composed of operant and operand resources. It proposes a definition for gamification, one that emphasizes its experiential nature. The definition highlights four important aspects of gamification: affordances, psychological mediators, goals of gamification and the context of gamification. Using the definition the article identifies four possible gamifying actors and examines gamification as communicative staging of the service environment.